Nutritional status assessment among elderly population in a rural area of South India - Palanivel Rajan, S.; Jeevithan, S.; Shanmugapriya, D.; Padmavathy, L. (International Journal Of Community Medicine And Public Health, 2020)
Background: With growing science and technology, the proportion of elderly population is increasing worldwide. Ageing with coupled with increased risk of malnutrition in elderly and is often the neglected part resulting in increased morbidity and mortality. Early identification and intervention of the malnutrition among elderly population plays a crucial role in improve the health of the elderly. Objective of the study was to estimate the prevalence of malnutrition among elderly in rural south Indian population. Methods: A Community based cross sectional study was conducted over a period of 2 months among 392 elderly population residing in a rural field practice area of a tertiary care hospital in Coimbatore. Elderly population both males and females > 60 years of age were screened for malnutrition and at risk for malnutrition using Mini Nutrition Assessment (MNA) tool. Data was analysed using Excel. p<0.05 were considered significant. Results: Majority of the study participants were in the age group of 60-70 years. 21.4% of the study participants were malnourished and 32.65% were at risk for malnutrition. The risk of malnutrition (40.57%) and malnutrition (25.71%) were high in females and is statistically significantly (p<0.05). Conclusions: Malnutrition among elderly is increasing at high rate even in rural areas. Early identification and intervention has to be done.